Implementation science challenges: hearing care professionals identify barriers to clinical research. - Meyer, Carly; Scarinci, Nerina; Lind, Christopher; Tulloch, Kristen; Atkins, Jenny; Hickson, Louise (International Journal of Audiology, 2024)
Conducting research in clinical settings is challenging. The aim of this study was to increase our understanding of hearing care professionals' perceptions of barriers to participating in such research. A modified group concept mapping approach was used to gain anonymous responses from 124 hearing care professionals to the statement: "One reason why it is hard to conduct intervention research studies in my centre/practice is....". Participants were asked for reasons other than 'time' as this is universally reported as a barrier to clinical research. A total of 107 distinct reasons were provided by participants and these were sorted into 5 clusters: "Competing demands/pressures" (18 statements), "Not a priority for management/organisation" (14 statements), "Lack of opportunity/support" (19 statements), "Clinician's knowledge, confidence, and beliefs" (24 statements), and "Recruitment/adherence to protocols is challenging" (32 statements). Identified barriers were generally similar to those reported in other healthcare settings, with unique barriers being those associated with a fear of scrutiny and lack of trust in the "academic elite". Findings highlight the importance of researchers, clinicians, and clinic managers working together at all stages of the research process in order for clinical research to be successful.